Poverty in Common: The Politics of Community Action During the American Century - Vibert, Elizabeth (Labour / Le Travail, 2013)
The article reviews the book, "Poverty in Common: The Politics of Community Action During the American Century," by Alyosha Goldstein.
Keywords: GOLDSTEIN; Alyosha; Nonfiction; POLITICAL participation; POVERTY in Common: The Politics of Community Action During the American Century (Book)